Exact solutions for some modifications of the nonlinear Cahn–Hilliard equation - Mchedlov-Petrosyan, P.O.; Kopiychenko, D.Yu. (Доповіді НАН України, 2013)
The exact travelling wave solutions for convective, higher-order convective, and convectiveviscous Cahn–Hilliard equations are obtained. Without any additional restrictions on the parameters, the solutions with non-zero propagation velocity exist only for an asymmetric potential.
However, for an additional constraint on the higher-order convective term or for a special
balance between nonlinearity and viscosity, the non-zero velocity exists for a symmetric potential
as well. In the latter case, the exact two-wave solution is obtained; asymptotically, it converges
to the well-known static kink solution. Отримано точнi розв’язки у виглядi бiжучої хвилi для конвективного, конвективного з бiльшим ступенем нелiнiйностi та конвективно-в’язкого рiвняння Кана–Хiлларда. Без будь-яких додаткових обмежень на параметри розв’язки з ненульовою швидкiстю iснують тiльки для асиметричного потенцiалу. Однак при додатковому обмеженнi на конвективний
член старшого ступеня або у випадку спецiального балансу мiж нелiнiйнiстю та в’язкiстю
розв’язки з ненульовою швидкiстю iснують i для симетричного потенцiалу. Для останнього випадку отримано i точний двохвильовий роз’язок; асимптотично вiн збiгається до вiдомого статичного кiнк-роз’язку. Получены точные решения в виде бегущей волны для конвективного, конвективного с более высокой степенью нелинейности и конвективно-вязкого уравнений Кана–Хилларда. Без
каких-либо дополнительных ограничений на параметры решения с ненулевой скоростью распространения существуют только для асимметричного потенциала. Однако при дополнительном ограничении на конвективный член старшего порядка или для случая специального баланса между нелинейностью и вязкостью решения с ненулевой скоростью существуют
и для симметричного потенциала. Для последнего случая получено и точное двухволновое
решение; асимптотически оно сходится к известному статическому кинк-решению.